Increased Hardness Value due to the Diffusion of Low-Temperature Carburizing Process - ., Nitha; Sutresman, Onny S; Aminy, Ahmad Yusran; Arma, Lukmanul Hakim (EPI International Journal of Engineering, 2023)
This research to determine the effect of the tensile load on the carburizing process and the heating temperature lower than the normal carburizing temperature on the hardness of carbon steel with a percentage of 80% buffalo bone charcoal and 20% BaCO3, 20 mesh grain size, 4 hours holding time, and slow cooling with a tensile load of 1/4σp 1/2σp 3/4σp, and σp (proportional stress). The heating temperatures below normal carburizing temperatures, namely 6000C, 6500C, 7000C, and 7500C while being pulled by 1/4σp, 1/2σp, 3/4σp, and σp. After reaching the heating temperature, the material is held in the furnace for 4 hours and cooled slowly. After the material is cold, mechanical testing is carried out with Vickers microhardness. Hardness value at a temperature of 6000C is 103.93 HRB, at a temperature of 6500C is 104.33 HRB, at a temperature of 7000C is 104.80 HRB, and at a temperature of 7500C is 106.60 HRB, while the process of pack carburizing without tensile at a heating temperature of 8000C is 105.2 HRB. This proves that the application of loads at lower heating temperatures during the heating process can exceed the hardness value without tensile loads at higher temperatures of 8000 C.